Partnering based on coopetition in the interorganizational networks of tourism: a comparison between Curitiba and Foz do Iguaçu, Brazil - Chim-Miki, Adriana Fumi (2017)
Purpose – This paper presents a model to analyze the context andcritical behavior of interorganizational partnering based on thecoopetition strategy.Design/methodology/approach – This research is exploratory, andmakes use of descriptive statistical methodology. Data collection wasbased on an entrepreneurial perception survey applied to 545 tourismfirms and 49 local business associations in two Brazilian cities.Findings – The main theoretical approach of this research was tointroduce a partnering model, and its variables, based on coopetition– whereas its main empirical finding was to prove that the highinternal competition among participants, within the tourism sector,is a greater source of coopetition behavior than external competitionitself. Shared values, mutual trust, complementarity and awareness ofthe competitive advantages that result from partnering co-exist withthe internal competition between firms belonging to this sector.Originality/value – Coopetition in the tourism sector has been littleexplored, but this study confirms that coopetition is a hybrid behaviorwhich is very suitable to explain current market relationships; it alsorepresents the interorganizational networks generated by businessassociations. The value of this research was to provide a scale to measurecooperative and competitive contexts on partnering based on thecoopetition strategy, which can be applied to other industries or sectors.